Single hair analysis by X-ray fluorescence spectrometry detects small changes in dietary zinc intake: A nested randomized controlled trial - Frederickson, Christopher J.; Fleming, David E. B.; Asael, Dan; Zaman, Mukhtiar; Ferguson, Randal; Kaiser, Michaela G.; Rankin, Bryn D.; Schenkels, Kassia M. M.; Hess, Andrew I. T.; Scott, Andrianna R.; Frederickson, Cathleen J. M.; Sinclair, Jonathan K.; et al. (Frontiers in Nutrition, 2023)
The aim of this study was to determine whether x-ray fluorescence spectrometry (XRF) could be used to detect changes in hair zinc concentration in response to a modest daily increase in zinc from the consumption of zinc biofortified wheat flour. This study was conducted as part of an effectiveness trial (BiZiFED2) exploring the potential for zinc biofortified wheat to alleviate zinc deficiency in adolescent girls aged 10-16 years in Pakistan (trial registration ID ISRCTN17107812). A randomised controlled design was used. Participants received either control flour or zinc biofortified flour for 6 months. Consumption of biofortified flour resulted in an average daily increase in dietary zinc intake of 1.5 mg per day above that of the control flour. At baseline and at the end of the intervention, individual hair samples (control: n= 59, intervention: n=64) were analyzed for zinc and sulphur content by XRF. Data were analysed using linear mixed effects models to contrast between trial groups the changes from baseline to end point and also to compare baseline and end point values within each trial group. Increases from baseline to endpoint in both sulphur and zinc were significantly greater in the intervention group compared to control (Sulphur counts. Control: baseline = 119.87±20.33 & endpoint = 121.58±23.58 / intervention: baseline = 122.67±24.19 & endpoint = 131.60±21.34); (Zinc counts. Control: baseline = 50.88±14.33 & endpoint =54.82±14.61 / intervention: baseline = 49.61±10.77 & endpoint = 58.79±12.20). For these parameters, there were also significant increases from baseline to endpoint in the intervention group but not in control. Furthermore, for Zn:S count ratio there were no differences in terms of the magnitude of the change from baseline to endpoint in the control group, although significant increases from baseline to endpoint were evident in the intervention group. (Zn:S count ratio. Control: baseline =0.42±0.10 & endpoint =0.45±0.08 / intervention: baseline =0.41±0.08 & endpoint =0.45±0.08). A modest increase in dietary zinc over 6 months resulted in a detectable increase in both sulphur and zinc counts in individual hairs measured using XRF. This offers a sensitive, non-invasive method to monitor changes within subjects in response to dietary zinc interventions.